The diversity of metaphorical graphic performance methods and their artistic and semantic impact in drawing the literary image according to Ibn al-Ameed (d. 360 AH) and Al-Sahib bin Abbad (d. 385 AH). A balancing study - Hamid Hashem Zabih Al-Tai; Dr.. Souad Badie Mutair (Journal of College of Education, 2024)
This research was concerned with revealing the diversity of methods of metaphorical graphic performance, and their artistic and semantic impact in drawing the literary image of the two literary ministers (Ibn al-Ameed and al-Sahib bin Abbad); Their metaphorical formation revealed the predominance of spatial metaphor, which represented the focus of semantic tension. It dominated their literary texts, thanks to its effectiveness in embodying various emotions and feelings, and its embodiment of inanimate objects, which gave their literary texts a distinctive suggestive and expressive dimension that worked to draw the minds of the listener to them, and added aesthetics to the connotations to be conveyed. Their metaphorical formation, both the verbal and the declarative, was characterized by clarity and distance from verbal complexity, with some points of agreement and difference between their methods, which were demonstrated by the balance.
Keywords: Performance, metaphor, Ibn al-Amin, al-Sahib ibn Abbas, the balance